2007
DOI: 10.1097/ta.0b013e3180d0a70e
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Site Surge Capacity in Times of Public Health Disaster Maintains Trauma Center and Emergency Department Integrity: Hurricane Katrina

Abstract: Alternate-site medical surge capacity provides for safe and effective delivery of care to a large influx of patients seeking urgent and emergent care. This protects the integrity of existing public hospital TC/ED infrastructure and ongoing operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 6 publications
0
38
0
1
Order By: Relevance
“…This centre, which was specifically designated to manage the surge of injured patients, quickly ran out of critical stores, taking almost a week to acquire adequate supplies. 15 The 2004 Indian Ocean tsunami damaged 61% of health facilities and killed 7% of health workers in the province of Aceh, Indonesia, limiting disaster relief. 23 Mass casualty incidents such as these have shown that a hospital's ability to function relies on lifelines and other basic services such as electrical power, waste management disposal, water and sanitation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This centre, which was specifically designated to manage the surge of injured patients, quickly ran out of critical stores, taking almost a week to acquire adequate supplies. 15 The 2004 Indian Ocean tsunami damaged 61% of health facilities and killed 7% of health workers in the province of Aceh, Indonesia, limiting disaster relief. 23 Mass casualty incidents such as these have shown that a hospital's ability to function relies on lifelines and other basic services such as electrical power, waste management disposal, water and sanitation.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15]17 We identified 6 domains as critical to disaster preparedness. These domains were leadership, hazard planning, communications, sustainability of peak operations, education and interagency cooperation.…”
Section: Survey Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…105 In areas that received large numbers of evacuees, EDs did experience significantly increased service demands, 111,112 although off-site activities helped blunt the expected surge in hard-hit sites such as Houston. 113 Of note, emergency physicians (EPs) were the last to leave New Orleans during Katrina. Overall, EPs were pivotal in the response, from on-site triage and care, care during transport, triage and stabilization on the receiving end, and ongoing care for displaced populations in their new environs.…”
Section: Climate Change Is Almost Certain To Alter the Severity Of Sementioning
confidence: 99%